(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
Assumptions concerning human relations and relationality abound within existential phenomenological literature. Nonetheless, significant differences exist with regard to both the status of such terms within existential thought and practice as well as to the specific meaning and interpretation to be given to them. This paper proposes to clarify matters through the consideration of three ‘Grand Theories’ each of which provides a distinct set of assertions regarding human relations derived from its focus on either individual subjectivity, intersubjectivity/subjectivity or relatedness. Following a brief discussion of each of these, the paper focuses on various analogous examples drawn from spiritual traditions, contemporary physics, the social sciences and consciousness studies in order to clarify key aspects of the third, and least well-known, ‘Grand Theory’. Further, it highlights key conclusions within this theory that resonate closely with those advocated by existential phenomenological literature. Finally, the paper argues that it is precisely this third ‘Grand Theory’ of relatedness that forms the basis for the radical ‘turn’ of existential phenomenology in general and existential therapy in particular.